A parallelization technique applied to the computation of rotating flows in cavities - Cunha, Rudnei Dias da; Bortoli, Álvaro Luiz de (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1999)
In this paper, we investigate the parallel solution to the rotating internal flow problems, using the Navier-Stokes equations as proposed in [ST83] and [SPE85]. A Runge-Kutta time-stepping scheme was applied to the equations and both sequential and message-passing implementations were developed, the latter using MPI, and were tested on an SGI Origin200 distributed, global shared memory parallel computer. The results show that our approach to parallelize the sequential implementation requires little effort whilst providing good results even for medium-sized problems, on this particular computer.